Pigmentation in Anuran Testes: Anatomical Pattern and Variation - Franco-Belussi, Lilian [UNESP]; Zieri, Rodrigo [UNESP]; De Souza Santos, Lia Raquel [UNESP]; Moresco, Rafaela Maria [UNESP]; De Oliveira, Classius [UNESP] (Wiley-Blackwell, 2009)
In amphibians, pigmented cells are present in several organs, composing an extracutaneous pigmentary system. Seventeen species from two families were studied to develop a protocol for pigmentary classification. The amount and distribution of these cells are variable, allowing the establishment of anatomical patterns for visceral pigmentation in anuran testes. Anat Rec, 292:178-182, 2009. (C) 2008 Wiley-Liss, Inc.
Keywords: Anurans; pigmentation testes; anatomical variation